2019
DOI: 10.3390/ma12121957
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, Structure and Properties of Ba-Doped Derivatives of SrCo0.95Ru0.05O3−δ Perovskite as Cathode Materials for SOFCs

Abstract: We have designed and prepared a novel cathode material for solid oxide fuel cell (SOFC) based on SrCo0.95Ru0.05O3−δ perovskite. We have partially replaced Sr by Ba in Sr0.9Ba0.1Co0.95Ru0.05O3−δ (SBCRO) in order to expand the unit-cell size, thereby improving the ionic diffusion of O2− through the crystal lattice. The characterization of this new oxide has been studied at room temperature by X-ray diffraction (XRD) and neutron powder diffraction (NPD) experiments. At room temperature, SBCRO perovskite crystalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The first weight loss interval (below 280°C) is attributed to the elimination of adsorbed substances (H 2 O, CO 2 ) from the sample surface. The change in mass loss at 280°C–600°C can be attributed to a fracture of the Fe–O bond leading to a lack of lattice oxygen (normalOnormalO×${\rm{O}}_{\rm{O}}^ \times $) in the surrounding atmosphere (Equations () and ()) 38,39 . The continued increase in oxygen loss associated with higher doping amounts indicates a rise in the oxygen vacancy (normalVnormalO··${\rm{V}}_{\rm{O}}^{ \cdot \cdot }$) concentration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first weight loss interval (below 280°C) is attributed to the elimination of adsorbed substances (H 2 O, CO 2 ) from the sample surface. The change in mass loss at 280°C–600°C can be attributed to a fracture of the Fe–O bond leading to a lack of lattice oxygen (normalOnormalO×${\rm{O}}_{\rm{O}}^ \times $) in the surrounding atmosphere (Equations () and ()) 38,39 . The continued increase in oxygen loss associated with higher doping amounts indicates a rise in the oxygen vacancy (normalVnormalO··${\rm{V}}_{\rm{O}}^{ \cdot \cdot }$) concentration.…”
Section: Resultsmentioning
confidence: 99%
“…The change in mass loss at 280 • C-600 • C can be attributed to a fracture of the Fe-O bond leading to a lack of lattice oxygen (O × O ) in the surrounding atmosphere (Equations ( 1) and ( 2)). 38,39 The continued increase in oxygen loss associated with higher doping amounts indicates a rise in the oxygen vacancy (V ⋅⋅ O ) concentration. The mass change observed to occur at 600 • C-800 • C can be attributed to a rupture of the Mo-O bond leading to a lack of lattice oxygen (Equation (3)).…”
Section: Physicochemical Characterizationmentioning
confidence: 99%
“…The chemical compatibility of La 1−x Sr x Ga 1−y Mg y O 3−δ was investigated with oxide materials used in SOFCs, cathodes [141][142][143][144][145][146][147][148][149][150][151][152] and anodes [153][154][155][156][157][158][159][160][161][162][163][164][165][166][167]: this is presented in the corresponding reviews [28,56,153].…”
Section: Sample Samples Obtaining Method; Annealing Temperature (°C) ...mentioning
confidence: 99%
“…Sydyknazar et al [143] showed that La 0.83 Sr 0.17 Ga 0.8 Mg 0.2 O 3−δ exhibited good chemical compatibility with a novel cathode material, Sr 0.9 Ba 0.1 Co 0.95 Ru 0.05 O 3−δ , after joint calcination at 1100 • C for 12 h. According to the literature, La 0.9 Sr 0.1 Ga 0.8 Mg 0.2 O 3−δ does not react with the following cathodes: La 0.4 Sr 0.6 Co 0.9 Sb 0.1 O 3−δ after heat treatment at 1150 • C for 6 h [144], SrCo 0.8 Fe 0.1 Nb 0.1 O 3−δ at 950 • C for 10 h [145], BaCo 0.7 Fe 0.2 Ta 0.1 O 3−δ at 950 • C for 10 h [146] and Sr 2 Ti 0.8 Co 0.2 FeO 6−δ after at 950 • C for 10 h [147]. According to Tarancón et al [148], La 0.8 Sr 0.2 Ga 0.8 Mg 0.2 O 3−δ interacted with a GdBaCo 2 O 5+δ cathode at temperatures above 900 • C, forming BaLaGa 3 O 4 and BaLaGa 3 O 7 secondary phases.…”
Section: Sample Samples Obtaining Method; Annealing Temperature (°C) ...mentioning
confidence: 99%
“…Therefore, it is necessary to stabilize the 3C phase in the temperature range in which a SOFC would normally operate. Much research has been conducted to stabilize this phase in a large temperature range, mainly by replacing some strontium [21][22][23][24] or cobalt [25][26][27] by aliovalent elements.…”
Section: Introductionmentioning
confidence: 99%